Laboratory performance study for passive sampling of nonpolar chemicals in water. (2nd December 2016) - Booij, Kees; Smedes, Foppe; Crum, Steven
Abstract: Two laboratory performance studies with 21 and 11 participants were carried out for passive sampling of nonpolar chemicals in water, using silicone samplers that were deployed for 7 wk and 13 wk at 2 river sites in the Netherlands. Target analytes were polychlorinated biphenyls, polycyclic aromatic hydrocarbons (PAHs), polybrominated diphenyl ethers (PBDEs), hexachlorobutadiene, hexachlorobenzene, and a number of performance reference compounds (PRCs). Calculation of aqueous concentrations based on prescribed input values and a prescribed uptake model was also included. Between‐laboratory coefficients of variation ( CV s) in the analysis of target compounds were approximately 20% at concentrations of 100 ng g −1 and approximately 100% at concentrations of 0.01 ng g −1, which was similar to previous results for the analysis of biota samples. The analysis of PRCs yielded water sampling rates with a between‐laboratory CV of 18% to 30%. The sampling rate model showed a nearly perfect match with the consensus values of retained PRCs. The implications of the present study for future interlaboratory exercises are discussed. Environ Toxicol Chem 2017;36:1156–1161. © 2016 SETAC